2015
DOI: 10.1039/c5cc00196j
|View full text |Cite
|
Sign up to set email alerts
|

The electronic effects of ligands on metal-coordination geometry: a key role in the visual discrimination of dimethylaminopyridine and its application towards chemo-switch

Abstract: Due to its special coordination ability to Cu(II)-terpyridine complexes, a simple and straightforward visual recognition of p-DMAP out of its analogues has been realized via selective metallogel collapse. In combination with the selective gel collapse and the self-healing properties of metallohydrogel , its potential application towards chemo-switch is also demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…In UV‐visible spectral studies, all the complexes showed three characteristic peaks which were found in the region near 407, 350, and 290 nm and clearly indicated the complexation of ligand with metal ion. [ 8,24,25 ] In IR spectroscopy, the azomethine peak in all the complexes was shifted towards lower frequency with respect to ligand except iron and copper complexes. In case of iron complex ( 2 ), it was found near 1,599 cm −1 while in case of copper complex ( 5 ) this has been found at 1,586 cm −1 .…”
Section: Resultsmentioning
confidence: 98%
“…In UV‐visible spectral studies, all the complexes showed three characteristic peaks which were found in the region near 407, 350, and 290 nm and clearly indicated the complexation of ligand with metal ion. [ 8,24,25 ] In IR spectroscopy, the azomethine peak in all the complexes was shifted towards lower frequency with respect to ligand except iron and copper complexes. In case of iron complex ( 2 ), it was found near 1,599 cm −1 while in case of copper complex ( 5 ) this has been found at 1,586 cm −1 .…”
Section: Resultsmentioning
confidence: 98%
“…A series of reported results of the coordination between Cu 2 + ions and carboxylate-rich substances through the X-ray crystallographica nalysis of MOFs are valuable for our study. [59][60][61][62][63] The most common coordination number of Cu 2 + is 5w ith the www.chemeurj.org square-pyramidal geometry,a sp rovenb yT ue tal., [63][64][65][66] and H 2 Om olecules usually bind to the metal center to complete the multiple coronation geometry. [59,62,63] The proposed schematic is shown in Scheme 2.…”
Section: Explanation Of the Mechanismmentioning
confidence: 99%
“…As an important family of molecules that have been formerly employed in the study of gel formation successfully, terpyridine compounds include terpyridine, which is functionalized at the central ring with an aromatic group, electron-withdrawing group, donating group, or heterocyclic substituents, such as furan, thiophene, oxazole, etc. Here, a complete survey of the gelation properties of a series of terpyridine and dipyrazine–pyridine ligands, CuCl 2 [Terpy- n CN] and CuCl 2 [Dipyz-py- n CN], where [Terpy- n CN] is 4′-( n -cyanophenyl)-2,2′,6′,2″-terpyridine and [Dipyz-py- n CN] is 4-( n -cyanophenyl)-2,6-di-pyrazin-2-yl-pyridine, Scheme , in the presence of metal salts is reported. In general, establishing H-bonding interactions, π–π stacking contacts, and metal coordination by using simple and easily available ligands, like those mentioned above, is feasible.…”
Section: Introductionmentioning
confidence: 99%